THE INFLUENCE OF FINTECH DIGITAL PAYMENT AND P2P LENDING ON INDONESIA’S ECONOMIC GROWTH - Yasir Maulana; Munir Nur Komarudin; Wely Hadi Gunawan; Ayus Ahmad Yusuf (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Studies suggest that financial innovations, or